Impacto da instabilidade do leite na qualidade e produção de queijo cottage - Biagini, Thamires Helena (My University, 2026)
The present study evaluated the occurrence of non-acid unstable milk (NAUM) in Holstein and Jersey herds in the Campos Gerais region, Paraná State, Brazil, and investigated the effect of its use on the production and physicochemical characteristics of Cottage cheese. Individual milk samples were collected from 120 cows throughout the four seasons of the year and analyzed for zootechnical parameters, physicochemical composition, alcohol stability, pH, titratable acidity, and somatic cell count. Alcohol stability showed seasonal variation and distinct behavior between breeds, with no consistent association with titratable acidity, reinforcing the multifactorial nature of NAUM. Cottage cheese was produced in batches using milk classified as stable and unstable in the alcohol test at 74% concentration, following a standardized technological protocol. The use of unstable milk resulted in higher apparent industrial yield, greater protein retention, and higher moisture content in the final product (p<0.05), while fat content showed a proportional reduction in both curd and cheese. In instrumental texture analysis, cheeses produced with unstable milk presented higher elasticity, cohesiveness, chewiness, and resilience values (p<0.05), with no significant differences observed for hardness and adhesiveness. Instrumental color evaluation revealed differences in a* and b* parameters, without significant changes in lightness (L*). Under the evaluated experimental conditions, milk protein instability promoted changes in physicochemical and technological parameters of Cottage cheese without compromising its manufacture. The results indicate that NAUM can be directed to the production of high-moisture fresh cheeses, provided that appropriate technological adjustments are applied.
Keywords: estabilidade do leite; gordura; proteína; tecnologia de laticínios; rendimento; dairy technology; fat; protein; stability of milk; yield